Assessing Suitable Habitats for Treefrog Species after Previous Declines in Costa Rica - Héctor Zumbado-Ulate (MDPI AG, 2021)
Treefrogs represent 22% of amphibian species in Costa Rica, but gaps in the knowledge about this group of amphibians can impede conservation efforts. In this study, we first updated the status of Costa Rican treefrogs and found that a total of 38% of treefrog species are threatened according to the most recent IUCN assessment in 2019. Additionally, 21% of Costa Rican treefrog species have a high vulnerability to extinction according to environmental vulnerability scores. Then, we predicted the historical climatic suitability of eight target species that we expected to have exhibited changes in their ranges in the last 20 years. We assessed the location of new occurrence records since 2000 to identify recovery, range expansion, or previously underestimated ranges due to methodological limitations. We also estimated the area of each species’ suitable habitat with two metrics: extent of suitable habitat (ESH) and area of minimum convex polygon (AMCP). Six declined species exhibited recovery (i.e., new occurrences across historical range after 2000), with the widest recovery found in Agalychnis annae. We also found that Isthmohyla pseudopuma appears to have spread after the decline of sympatric species and that the range of I. sukia was originally underestimated due to inadequate detection. We found that the ESH was 32–49% smaller than the AMCP for species that are slowly recovering; however, the ESH is similar or greater than the AMCP for species that are recovering in most of their ranges, as well as rare species with widespread ranges. Results of this work can be used to evaluate the risk of environmental threats and prioritize regions for conservation purposes.